Ex Vivo Evaluation of Secretion-Clearing Device in Reducing Airway Resistance within Endotracheal Tubes - Christopher Waters; R. Constance Wiener; Hamed M. Motlagh (Critical Care Research and Practice)
Background. Secretions accumulate in endotracheal tubes’ (ETT) lumens upon their placement in patients. The secretions impact airway resistance and pressure. Secretions potentiate prolonged mechanical ventilation and ventilator-associated pneumonia. Our primary objective in this study was to evaluate an ETT-clearing device (ETT-CD) in its ability to remove secretions from ex vivo ETT lumens. Methods. Forty ETTs, obtained from intensive care patients at extubation, were individually placed into a ventilator field performance testing simulator at 37°C. The pressure drop through the ETTs was measured at a flow rate of 60 L/min before and after cleaning with the ETT-CD and compared with unused, similarly sized controls tubes. The ETT-CD was inserted into an ETT until the tip reached Murphy’s eye (hole in the side) of the ETT. The wiper, set back from the tip, was expanded by ETT-CD handle activation. As the ETT-CD was removed, the distal wiper extracted secretions from the ETT lumen. Results. Forty ETTs were tested with nonparametric Wilcoxon signed-rank tests. Before being cleared with the ETT-CD, the median pressure drop in the extubated 7.5 mm ETTs was 17.8 cm H2O; after ETT-CD use, it was 12.3. The cleared ETTs were significantly improved over the ETTs before being cleared (p<0.001); however, there remained a significant difference between the cleared ETTs and the control tubes (p=0.005), indicating the clearing was not to the level of an unused ETT. Similar results were determined for the 8.0 mm ETTs. Conclusions. For the 7.5 mm and the 8.0 mm EETs, the ETT-CD improved effective patency of the ETTs over the uncleared ETTs, independent of occlusion location, tube size, or length of tube. However, there remained a significant difference between the cleared tubes and controls.